2014
DOI: 10.1093/infdis/jiu621
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Levels and Risk of HIV Type 1 (HIV-1) Transmission and Acquisition: A Nested Case-Control Study Among HIV-1–Serodiscordant Couples

Abstract: Immune activation, as measured by levels of cytokine markers, particularly elevated levels of IL-10 and CXCL1, are associated with increased HIV-1 susceptibility and infectiousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…In fact, it has been reported that BCG vaccination in South African newborns induced an increase in CCR5 ϩ and in HLA-DR/CD38 ϩ -expressing CD4 ϩ T cells (11,12), raising the question of whether BCG-induced CD4 ϩ T cell activation might increase the risk of HIV-1 acquisition in the pediatric population. Further, immune activation in the intestine or other sites of virus entry has been associated with increased HIV or SIV acquisition in humans and in nonhuman primates (59)(60)(61)(62)(63)(64). This conclusion is supported by our findings that infant macaques vaccinated with AMtb or BCG vaccines had increased CD4 ϩ CCR5 ϩ T cells in blood and in tissues that serve as presumed entry sites for SIV after oral exposure.…”
Section: Trained Immunity and Immune Activation Of Tb Vaccinessupporting
confidence: 71%
“…In fact, it has been reported that BCG vaccination in South African newborns induced an increase in CCR5 ϩ and in HLA-DR/CD38 ϩ -expressing CD4 ϩ T cells (11,12), raising the question of whether BCG-induced CD4 ϩ T cell activation might increase the risk of HIV-1 acquisition in the pediatric population. Further, immune activation in the intestine or other sites of virus entry has been associated with increased HIV or SIV acquisition in humans and in nonhuman primates (59)(60)(61)(62)(63)(64). This conclusion is supported by our findings that infant macaques vaccinated with AMtb or BCG vaccines had increased CD4 ϩ CCR5 ϩ T cells in blood and in tissues that serve as presumed entry sites for SIV after oral exposure.…”
Section: Trained Immunity and Immune Activation Of Tb Vaccinessupporting
confidence: 71%
“…A woman reported situation in which she obtained a restraining order but her abusive partner violated it: The restraining order didn’t do no good, because 23 said, “It’s just a piece a paper. It’s not going to stop me.” And he proved it that it was not going to stop him.…”
Section: Resultsmentioning
confidence: 99%
“…The restraining order didn’t do no good, because 23 said, “It’s just a piece a paper. It’s not going to stop me.” And he proved it that it was not going to stop him.…”
Section: Resultsmentioning
confidence: 99%
“…Blood biomarkers have also been associated with increased risk of HIV infection [25,26]. Others from our group reported that women who later became HIV-infected had higher plasma concentrations of TNF-α, IL-2, IL-7, and IL-12p70 than women who remained uninfected [25].…”
Section: Systemic Markers Of Inflammation Chemokine Gradients and Himentioning
confidence: 99%
“…We found that these and other cytokines do not correlate between blood and the genital tract, suggesting that cytokine risk factors identified in blood do not predict those in the genital tract and vice versa [9,27]. Kahle et al found that elevated plasma IP-10 and IL-10 concentrations predicted HIV seroconversion in individuals in HIV discordant relationships [26]. …”
Section: Systemic Markers Of Inflammation Chemokine Gradients and Himentioning
confidence: 99%